Dietary changes are associated with an increase in air pollution-related health and environmental inequity in China - Biao Luo; Jianwei Huang; Xueying Liu; Mei-Po Kwan; Amos P. K. Tai (Communications Earth & Environment)
Abstract Agriculture is an important contributor to air pollution and its health impacts, with ramifications for environmental and health inequity. A substantial fraction of these effects can be attributable to dietary changes, but the extent of such impacts remains unclear. Here we show that the PM2.5-related mortality attributable specifically to dietary changes and the associated rising agricultural emissions has a high Gini coefficient of 0.369 in China in 2010, and raises the Gini coefficient of all-cause PM2.5-related mortality from 0.189 to 0.197 with more uneven allocation among income groups, reflecting worsened health inequity and an export of pollution from richer coastal regions to poorer agricultural regions via food trade. Such mortality is associated positively with urbanization but negatively with green space and healthcare quality. Our results also provide empirical evidence for the environmental Kuznets curve hypothesis, and offer decision support for equitable clean air, food and health policies in China.